Suguh Hati As An Alternative Form Of Land Dispute Settlement In Plantation - Kusbianto, Kusbianto (Universitas Dharmawangsa, 2025)
This study examines the practice of suguh hati as an alternative form of land dispute resolution in plantations, especially in PT Perkebunan Nusantara (PTPN) in North Sumatra. Land disputes in the plantation sector often arise due to differences in views between Indigenous Peoples regarding communal land tenure rights with the concept of positive law that places the state as the ruler of the land. The mediation and treat heart approach is a non-litigation effort that is used to avoid horizontal conflicts and maintain social relations between the company and the tenant community. Treat the heart is understood as a form of moral and social compensation that reflects the goodwill and faith of mutual trust between the parties to the conflict. Through the decree of the Board of Directors of PTPN III number 3.11/SKPTS/01 / 2015, suguh hati was instituted internally as a legitimate dispute resolution instrument. The results showed that suguh hati is not just a social practice, but has developed into IUs factum which has the potential to become IUs constitutum, the source of new laws in National Agrarian Reform. These findings make an important contribution to the development of agrarian law and land dispute resolution in Indonesia that is more humane, participatory, and based on local wisdom.